Marmin of Aegle Marmelos Correa Antagonizes AChM3 Receptors: In Silico and In Vitro Studies on Isolated-Guinea Pig Illeum Smooth Muscle - Nugroho, Agung Endro; Noviarsito, Puguh; Riyanto, Sugeng (Journal of Mathematical and Fundamental Sciences, 2014)
Marmin is a coumarin derivative compounds isolated from the bark and roots of Aegle Marmelos Correa. Previously, ethanolic extract of leaves of Aegle Marmelos Correa on isolated ileum showed antagonism effect on the contraction induced by histamine. Besides H1 receptor, there is also muscarinic acetylcholine (AChM)receptors involved in the mechanism of ileum contraction. Marmin is predicted to antagonize on AChM3 receptors.This study aimed to determine the effect of marmin on smooth muscle contraction of isolated guinea pig ileum induced by metacholine, an agonist of AChM3 receptor. The method in the study were in vitro (isolated organ) and in silico (docking PLANTS). In the in vitro study, marmin exhibited a competitive antagonists effect at the concentration of 100 Î¼M (pA2 value of 1,728) on the AChM3 receptors. Reversibility assay on AChM3 receptors showed that by washing the ileum with Tyrode buffer every 6 minutes for 30 minutes, the bond of marmin to the receptor was still not completely detached. In the in silico study, marmin was observed to be bound to AchM3 receptors (docking score: -102.086). Marmin bond was weaker than that of native ligand of AChM3 receptor (tiotropium, docking score: -115.107), however, stronger than that of AChM3 receptor agonist and antagonist. Based on the results, we conclude that marmin have a competitive antagonist activity on AChM3 receptor.